Efficiency assessment of listed real estate companies: an empirical study of China - Zheng, Xian; Chau, Kwong-Wing; C. M. Hui, Eddie (International Journal of Strategic Property Management, 2011)
This study measures performance and efficiency of the Listed Real Estate Companies (LRECs). Three types of Data envelopment analysis (DEA) approaches are employed, which are CCR-DEA, BCC-DEA and Super-Efficiency-DEA models. Based on these DEA approaches, we conduct an empirical analysis on the 94 LRECs in China stock markets according to the 2009 Annual Financial Statements. Registered Capital, Asset Value, Employee Number, and Operation Cost are adopted as the inputs factors, while the output factors are denoted by Revenue and Profit. In general, this empirical research delivers four outcomes: firstly, an integrated assessment system and a ranking of the LRECs are established, which provides useful information for investors who are seeking for indirect exposure in the Chinese real estate market. Secondly, the average Overall Efficiency (OE), Pure Technical Efficiency (PTE) and Scale Efficiency (SE) of the LRECs are 0.78, 0.84 and 0.92 respectively. Thirdly, 69% of the inefficient LRECs are classified as increasing returns to scale and could further increase operating efficiency by scale expansion. Fourthly, the employees slack is prevalent at 18.96% for the inefficient LRECs. First Publish Online: 4 Jul 2011